Psychological Status During Menopausal Transition in Women With Polycystic Ovarian Syndrome Living in a Frontline City: A Cross‐Sectional Study in Kharkiv, Ukraine - Lakhno, Igor (John Wiley & Sons Ltd., 2026)
Background: Polycystic ovarian syndrome (PCOS) is an evolutionary disease that negatively affects reproductive, dermatological, cardiovascular and psychological aspects of health. The study was focused on the investigation of the relationship between PCOS and clinical, biochemical and psychological features in perimenopausal women in the frontline city of Kharkiv. Material and Methods: A descriptive cross‐sectional study was conducted in 68 perimenopausal women who were enroled in the study. The 38 women without prior PCOS were included in Group I. The 30 women with a history of PCOS were enroled in Group II. The variables of body mass index (BMI), heart rate (HR) and blood pressure (BP) were measured at inclusion. The menopausal Cooperman's score and psychological tests were assessed. The latter were Spielberger's scale (personal and reactive anxiety), Taylor's anxiety measurement and the Perceived Stress Scale (PSS). The acceleration capacity (AC) and deceleration capacity (DC) via electrocardiography were detected. The atherogenic index (AI), which reflects the ratio of atherogenic and antiatherogenic fractions of cholesterol, was calculated. Homeostatic Model Assessment (HOMA) index was detected. C‐reactive protein (C‐RP) as a marker of chronic inflammation was investigated. Results: The variables of BMI, HR, systolic BP, diastolic BP, Cooperman's score, HOMA index, AI, C‐RP and AC/DC did not differ significantly between the study groups. However, the level of anxiety and stress variables was significantly higher in women with prior PCOS in Group II. The variable of BMI demonstrated moderate correlation with HOMA index (r = 0.33, p = 0.006) and C‐RP (r = 0.43, p < 0.001). The systolic BP had a strong or moderate correlation with diastolic BP (r = 0.74, p < 0.001), HR (r = 0.53, p < 0.001) and Cooperman's score (r = 0.45, p < 0.001). Similar trends were found in diastolic BP: diastolic BP versus systolic BP (r = 0.74, p < 0.001), diastolic BP versus HR (r = 0.52, p < 0.001) and Cooperman's score (r = 0.54, p < 0.001). HR correlated with Taylor's anxiety measurement (r = 0.27, p = 0.028). Cooperman's score demonstrated a relationship with systolic BP (r = 0.45, p < 0.001), diastolic BP (r = 0.54, p < 0.001), AC (r = −0.28, p = 0.021) and DC (r = −0.27, p = 0.027). Moderate correlation was found in the pairs HOMA index versus BMI (r = 0.33, p = 0.006), HOMA index versus C‐RP (r = 0.45, p < 0.001) and HOMA index versus PSS (r = −0.35, p = 0.040). The relationship between AI and Taylor's anxiety measurement (r = −0.3, p = 0.014) was detected. The multivariate logistic regression detected the link between Spielberger's scale score and prior PCOS. The found coupling between Spielberger's scale score and PSS demonstrated a mutual nature of these scales' parameters. Conclusion: PCOS was a reason for psychological disorders in perimenopausal women residents of a frontline city of Kharkiv. While metabolic profiles between women with and without a history of PCOS could equalize with age, PCOS served as a primary trigger for significantly higher psychological distress under wartime conditions. Therefore, healthcare programmes for this demographic must integrate psychological support and potentially pharmacological interventions (sedatives, anxiolytics or HRT).
Keywords: Polycystic ovarian syndrome; wartime stress; female health; menopause; psychological disorders; 2026а